The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/scs.12799
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perspective on their responsibilities with regard to adolescents’ use of alcohol

Abstract: Parents' perspective on their responsibilities with regard to adolescents' use of alcohol Background: Parents have responsibilities when their adolescent offspring use alcohol, but little is known about their views on the topic. This knowledge would help healthcare organisations to develop practices to help parents meet their responsibilities. Aim: The aim of this study was to describe parents' perceptions and experiences of their responsibilities and what support they needed to tackle underage drinking. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Using NVivo software helped us to achieve our research objectives, as this made the analysis process more systematic and helped us to increase the credibility. The uniformity of the secondary data, and their credibility with the qualitative original studies 28,32 confirmed their internal validity. The data collection and analysis process have been described in detail to enable transferability.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Using NVivo software helped us to achieve our research objectives, as this made the analysis process more systematic and helped us to increase the credibility. The uniformity of the secondary data, and their credibility with the qualitative original studies 28,32 confirmed their internal validity. The data collection and analysis process have been described in detail to enable transferability.…”
Section: Discussionmentioning
confidence: 69%
“…This was a deductive secondary analysis that explored the original datasets 28,32 of two studies conducted in Eastern Finland in 2017 (Figure 1). We used the consolidated criteria for qualitative research to ensure explicit and comprehensive reporting of the study and to improve its rigor, comprehensiveness, and credibility 33 .…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has focused on responsibilities for adolescents' alcohol use from their own developmental perspective [23] and from their parents' point of view [24]. Research has mainly focused on adolescents' alcohol consumption [25] and its consequences [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Support from families, schools and peers has been found to prevent, and reduce, adolescents' drinking [26,27]. However, we need to know more about adolescents' own perspectives of their responsibilities with regard to their alcohol use and what support adolescents feel they need [24,28]. The Finnish Alcohol Act (1102/2017) states that people under 18 years of age are not allowed to buy or consume alcohol [29].…”
Section: Introductionmentioning
confidence: 99%